Styles of teaching Science compared to job seniority and teacher’s education. The student’s perspective12 - Czapla , Małgorzata; Rataszewska, Agata (Kultura-Społeczeństwo-Edukacja, 2020)
Czapla Małgorzata, Rataszewska Agata, Styles of teaching Science compared to job seniority and teacher’s education. The student’s perspective. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 95–114, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.7. The article presents the manner of work of science teachers on the basis of students’ opinions. The research included 870 6th grade primary school students, whose teachers had different work experience and level of education. The authors used the diagnostic survey as the research method. Flander’s analysis category system was used for the analysis of classroom interactions. In order to establish the relationship between the pairs of quality variables, the chi-square test of independence was used. It has been found that the teaching style is consistent with an adopted teaching model. There are two main types of teaching models: a model based on cognitive psychology and behavioural psychology. The model is reflected in the teacher’s teaching style, which might be reactive or directive. In the students’ opinion science teachers, particularly those with the shortest work experience, most often transmit their knowledge to students during classes (directive style). Those with more seniority and experience encourage students to perform certain tasks more frequently (reactive style). Science teacher’s education does not influence the teaching style and the majority of teachers prefer a syncretic style. Students of the teacherspreferring a directive style revealed lower interest in sciencethan those who were taught in reactive style.As a result of this disinterest, the studied students only occasionallyperformed activities in direct contact with nature.